2024
DOI: 10.1002/pc.28182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon nanotubes on thermoset curing and mechanical properties of carbon fiber reinforced epoxy resin laminates fabricated by self‐resistance electric heating

Hongming Zhang,
Gaoyin Zhao,
Xin Li
et al.

Abstract: Self‐resistance electric (SRE) heating for the curing of carbon fiber reinforced plastic (CFRP) offers the benefits of saving energy consumption and reducing investment in equipment. In this work, the investigation was carried out to illustrate the effect of carbon nanotubes (CNTs) addition (0.5, 1.0, and 1.5 wt%) on the thermoset curing and mechanical properties of carbon fiber‐reinforced epoxy laminates fabricated by SRE heating method. The results show that adding CNTs can improve the temperature uniformity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…With the electrical conductivity and the Joule heating effect of fillers, the self-resistance electric heating is of great interest, given that it has shorter preparation time, lower energy consumption, and higher mold dimensional stability compared to using the external heat source [27][28][29]. Zhang et al [30] investigated the mechanical properties of carbon fiber reinforced epoxy laminates fabricated by the self-resistance electric heating. They found that the content of carbon nanotubes addition could improve the thermoset curing performance and mechanical properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…With the electrical conductivity and the Joule heating effect of fillers, the self-resistance electric heating is of great interest, given that it has shorter preparation time, lower energy consumption, and higher mold dimensional stability compared to using the external heat source [27][28][29]. Zhang et al [30] investigated the mechanical properties of carbon fiber reinforced epoxy laminates fabricated by the self-resistance electric heating. They found that the content of carbon nanotubes addition could improve the thermoset curing performance and mechanical properties of the composites.…”
Section: Introductionmentioning
confidence: 99%